Pengaruh Work Life Balance, Reward, dan Pengawasan terhadap Disiplin Kerja: (Studi Kasus Pada Karyawan PT Kharisma Autokreasi Permai di Kota Tangerang) - Nur Azizah; Widi Wahyudi (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to determine the influence of work-life balance, reward and supervision on work discipline. The sampling technique used is Non Probability Sampling with a sample of 40 respondents. The data in this study was collected using a questionnaire. Data analysis techniques include classical assumption tests, correlation coefficients, multiple linear regression analysis, determination coefficients, and hypothesis tests (t-tests). This study uses the IBM SPSS application version 25. The study results show that work life balance has a positive and significant effect on the work discipline of PT Kharisma Auto Kreasi Permai employees in Tangerang City. Rewards do not have a significant effect on the work discipline of PT Kharisma Auto Kreasi Permai employees in Tangerang City. Supervision has a positive and significant effect on the work discipline of PT Kharisma Auto Kreasi Permai employees in Tangerang City. The conclusion of this study shows that work life balance and supervision have a positive and significant effect on work discipline, while rewards do not have a significant effect on work discipline.